Respuesta :
g(3) = -2(3) + 1
g(3) = -6 + 1 = -5
f(-5) = 4(-5) - 2
f(-5) = -20 -2
f(-5) = -22
Hence, the value of f(g(3)) is equal to -22.
g(3) = -6 + 1 = -5
f(-5) = 4(-5) - 2
f(-5) = -20 -2
f(-5) = -22
Hence, the value of f(g(3)) is equal to -22.
Value of f(g(3)) is -22.
What is a function?
Function is an expression, rule, or law that defines a relationship between one variable (the independent variable) and another variable (the dependent variable).
Given
f(x) = 4x – 2
g(x) = -2x + 1
Value of f(g(3))
g(x) = -2x + 1
g(3) = -2(3) + 1
g(3) = -6 + 1
g(3) = -5
f(g(3)) = f(-5)
f(x) = 4x – 2
f(-5) = 4(-5) - 2
f(g(3)) = -20 -2
f(g(3)) = -22
Hence, value of f(g(3)) is -22.
Find out more information about function here
https://brainly.com/question/17142336
#SPJ2